Elucidating the role of inflammatory mediators in frozen shoulder - Gacaferi, H (2023)
Frozen shoulder is a painful inflammatory fibrotic disease of the glenohumeral joint capsule. While it’s frequently self-limiting, patients can be symptomatic for years. The underlying pathophysiology of frozen shoulder is not fully understood, hampering the development of an effective therapy. Increased expression of inflammatory mediators has been identified in frozen shoulder, suggesting a potential role for these mediators in disease. However, the precise cellular interactions and the cell types expressing inflammatory mediators have not been identified.